Forecasting of phenotypic productivity of middle-early soybean varieties - О. І. Присяжнюк; В. Г. Димитров; О. М. Мартинов (Plant Varieties Studying and Protection)
Purpose. To study biological characteristics of growth and development of middle-early soybean varieties and create a model of phenotype productivity.